Transfection-Induced Defects in Dynein-Driven Transport: Evidence that ICs Mediate Cargo-Binding - Towns, William L. (2009)
Cytoplasmic dynein contributes to the localization and transport of multiple membranous organelles, including late endosomes, lysosomes, and the Golgi complex. It remains unclear which subunits of dynein are directly responsible for linking the dynein complex to these organelles, however the intermediate chain (IC), light intermediate chain (LIC) and light chain (LC) subunits are each thought to be important. Based on previous mapping of a dynein IC phosphorylation site (S84), we measured the impact of transfected ICs on dynein-driven organelle transport (Vaughan et al., 2001). Wild-type and S84A constructs disrupted organelle transport, whereas the S84D construct induced no defects. In this study we investigated the mechanisms of transfection-induced disruption of organelle transport. Transfected ICs did not: 1) disrupt the dynein holoenzyme, 2) incorporate into the native dynein complex, 3) dimerize with native dynein ICs or 4) sequester dynein LCs in a phosphorylation-sensitive manner. Consistent with saturation of dynactin as an inhibitory mechanism, truncated ICs containing only the dynactin-binding domain were as effective as full-length IC constructs in disrupting organelle transport, and this effect was influenced by phosphorylation-state. Competition analysis demonstrated that S84D ICs were less capable than dephosphorylated ICs in disrupting the dynein-dynactin interaction. Finally, two-dimensional gel analysis revealed phosphorylation of the wild-type but not S84D ICs, providing an explanation for the incomplete effects of the wild-type ICs. Together these findings suggest that transfected ICs disrupt organelle transport by competing with native dynein for dynactin binding in a phosphorylation-sensitive manner.